Pengaruh Pelat Pengarah (Buffle) Terhadap Distribusi Temperatur Cold Storage Skala Kecil - Supiyanto, Supiyanto; Qiram, Ikhwanul; Rubiono, Gatut (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2017)
Banyuwangi has a potency as a fishery region. At certain season, the fish production has maximum number. Cold storage is a cooling apparatus which can be used to maintain fish freshness. This research is aimed to get the effect of buffle angle due to temperature distribution of small scale cold storage. The research conduct using model of cold storage with 40 cm length, 30 cm wide and 30 cm height. The model made from styrofoam material. Buffle angle vary as 40o, 50oÂ dan 60o. Volume flow cooling rate vary with fan voltage input as 6, 9 and 12 Volt. Temperature data are taken using K type thermocouple at 4 measurement points which positioned at the center of cold storage. The result shows that buffle angle has effect due to temperature distribution. The most efficient angle is 60o. The lowest temperature happen at 30 ml/s volume flow rate which is 16,3oC.